Repeated balloon inflation under low pressure may reduce serious adverse events during endoscopic papillary large balloon dilation. (5th June 2021) - Kamada, Hideki; Kobara, Hideki; Yamana, Hiroki; Fujita, Naoki; Namima, Daisuke; Kohno, Toshiaki; Hirata, Masahiro; Nakabayashi, Ryota; Okano, Keiichi; Masaki, Tsutomu
Abstract : Highlight Kamada and colleagues devised a new technique for effective endoscopic papillary large balloon dilation without high balloon pressure. Advantages of the technique include the prevention of unintentional over‐pressurization of the balloon by limiting the balloon inflation pressure and reduced risk of pancreatitis due to continuous pancreatic duct obstruction.